(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research examines the ingredients of the various calcium hydroxide preparations used in restorative dentistry. The significance of specific elements in regard to the qualities of such substances and their mode of therapeutic action in relation to the dentine pulpal response and antibacterial activity is explored. Also covered are the use of calcium hydroxide in restorative dentistry.